Characteristics Of Attacus atlas Cocon Collected from Tree of Mahoghony (Swietenia mahagoni) in Kembaran District - Nofa Yulistiana Putri; Juli Rochmijati Wuliandari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Attacus atlas is a wild silk type from the non-mulberry group, representing various fagara silkworms that produce cocoons. The produced cocoons have high economic value when utilized for commercial silk production. The distinctive characteristic of A. atlas silk fibers differs from Bombyx mori (mulberry) silk as the resulting fibers have a natural brown color without dyeing processes. The characteristics of cocoons significantly impact the resulting thread production. This study aims to obtain data on the characteristics and morphometrics of A. atlas cocoons located on mahogany trees providing road shade in Kembaran District. Observed characteristics include the weight of the intact cocoon skin, the weight of cocoon skin without floss, the weight of floss, cocoon diameter, cocoon circumference, cocoon length, and cocoon color. The collected data were then analyzed using descriptive analysis. The research shows that A.atlas cocoon skin characteristics vary greatly, demonstrated by the weight of the intact Cocoon Skin (0.66-2.35 g), the weight of Cocoon Skin without Floss (0.46-1.93 g), the weight of Floss (0.1-0.54 g), Cocoon Length (5.2-8.1 cm), Anterior Diameter (2.10-3.0 cm), Medial Diameter (2.30-3.4 cm), Posterior Diameter (2.20-3.1 cm), Anterior Circumference (6.20-9.50 cm), Medial Circumference (7.70-10.50 cm), Posterior Circumference (6.10-9.10 cm), and cocoon color classification into light (17 cocoons/15.9%), medium (66 cocoons/61.7%), and dark (24 cocoons/22.4%). The temperature, cocooning location, and gender of the cocoon are unknown, resulting in weight and morphometric value variations.